Thermionic injection analysis in germanium nanowire Schottky junction FETs by means of 1D and 3D extraction methods - Behrle, Raphael; Pacheco-Sanchez, Aníbal; Barth, Sven; Weber, Walter M; Sistani, Masiar (Nanoscale advances, 2025)
Schottky barrier field-effect transistors (SBFETs) are a promising family of devices suitable for realizing "Beyond CMOS" paradigms. As the SBFET device operation is strongly dependent on the metal-semiconductor junction properties, it is important to extract and understand the activation energy to inject charge carriers into the semiconductor channel. In this regard, the three-dimensional (3D) thermionic emission (TE) and the one-dimensional (1D) Landauer-Büttiker (LB) theory are among the most sophisticated methods. Here, both methods are used to analyze the charge carrier injection capabilities of Al-Ge-Al nanowire (NW) heterostructure SBFETs. While the 3D TE model underestimates the activation energy E a in strong accumulation, at the intrinsic off-point, where merely TE contributes to charge carrier transport, both models provide reasonable values close to the theoretically expected Schottky barrier height. Analyzing the underlying mathematical models of 3D TE and 1D LB reveals a quadratic and linear increase in TE depending on temperature, respectively. Moreover, until now effects on the E a originating from the 1D nature of the proposed device were rarely investigated in NW transistors. This comparison contributes to a better understanding and the advancement of SBFET devices and circuit technologies. The carrier transport in Ge-based nanowire transistors is analyzed by temperature-dependent electrical measurements and discussed in terms of three-dimensional thermionic emission and one-dimensional Landauer-Büttiker theory.